Laser‐Driven Strong‐Field Terahertz Sources. Issue 3 (3rd December 2019) - Fülöp, József András; Tzortzakis, Stelios; Kampfrath, Tobias
Abstract: A review on the recent development of intense laser‐driven terahertz (THz) sources is provided here. The technologies discussed include various types of sources based on optical rectification (OR), spintronic emitters, and laser‐filament‐induced plasma. The emphasis is on OR using pump pulses with tilted intensity front. Illustrative examples of newly emerging applications are briefly discussed, in particular strong‐field THz control of materials and acceleration and manipulation of charged particles. Abstract : A review on recent development of intense laser‐driven terahertz sources is provided. The technologies discussed include optical rectification (OR), spintronic emitters, and laser‐filament‐induced plasma. The emphasis is on OR using pump pulses with tilted intensity front. Examples of newly emerging applications are presented in strong‐field THz control of materials and acceleration and manipulation of charged particles.